Nature-based interventions: a systematic review of reviews - Kaleta, Branislav; Campbell, Stephen; O’Keeffe, Jimmy; Burke, Jolanta (Frontiers in Psychology, 2025)
BackgroundNature-based interventions are emerging as an alternative to therapeutic approaches aimed to reduce and prevent mental and physical ailments. However, little is known of the types of interventions available to use by healthcare professionals. This systematic review of reviews aimed to classify and categorise different types of Nature-Based Interventions (NBIs) which currently exist under different names and approaches. The second aim of our review was to explore the mediating and moderating factors impacting NBI effectiveness.MethodsThe systematic review used the narrative synthesis approach following the PRISMA guidelines, using the following databases: Academic Search Complete, APA PsycInfo, CINAHL, MEDLINE, and included only peer-reviewed review articles in English which explored Nature Based Interventions (NBIs), excluding animal-based interventions. The quality review was conducted using AMSTAR-2.ResultsThe review included a total of 61 reviews of NBIs, covering 13 different categories of NBIs: nature-based interventions, horticulture, nature exposure, green exercise, wilderness and adventure therapy, forest therapy, blue space interventions, care farming, nature play, nature-based education, environmental volunteerism, immersive nature experiences, and caring for country. Furthermore, 11 moderating and mediating factors influencing NBI effectiveness were identified: social, physical activity, age, nature connectedness, duration and frequency, gender, symptom severity, environment type, participant motivation and preference, challenge confrontation, and autonomy, responsibility, and skill and knowledge acquisition.ConclusionThe current review found a wide variety of NBIs, showcasing the many different options available to individuals and healthcare professionals offering accessible and cost-effective NBIs. Moreover, the moderating and mediating factors identified in our review will help future researchers, healthcare professionals, and practitioners consider these factors when evaluating the effectiveness of NBIs.Systematic review registrationPROSPERO (https://www.crd.york.ac.uk/PROSPERO/view/CRD42023491598), identifier (CRD42023491598).